Factors Affecting Interest In The Use Of Electronic Money In Ovo Applications - Widya Paramita DEWI; A.A. Ketut JAYAWARSA; A.A Sri PURNAMI (Indonesia Strategic Sustainability, 2021)
There are factors that influence the use of Electronic Money in the OVO Application, such as Ease and Security. OVO is a product (e-money) issued by PT. International Visionet Data. This application is used as a transaction medium in making payments with electronic payment methods digitally based on data obtained by the use of (e-money) is increasing and in demand by the Indonesian people from year to year continues to increase, even at the end of September 2019 the amount of Electronic Money has jumped 31 times folded to 25.1 million units. This proves that the level of Ease and Security provided by the OVO Application is very good. From the research results obtained results, where Ease has a positive and partially significant influence on the Interest in Using Electronic Money in the OVO Application for Students of the Faculty of Economics and Business, Warmadewa University, besides that security, has a positive and significant commercial effect on the interest in using Electronic Money in Economics Faculty Students and Warmadewa University Business. The convenience and security provided by the OVO Application is sufficient to attract interest in the use of Electronic Money by consumers, advised for the OVO Application to pay more attention and increase its convenience and security.